Alternative products for the protection of vine against downy mildew - Pereira, Vanessa Foresti; Resende, Mário Lúcio Vilela de; Monteiro, Ana Cristina Andrade; Júnior, Pedro Martins Ribeiro; Regina, Murillo de Albuquerque; Medeiros, Fernanda Carvalho Lopes (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the efficiency of alternative products for the protection of vine (Vitis vinifera) against downy mildew (Plasmopara viticola), and to determine the influence of these products on the quality of Merlot cultivar grapes. Products based on plant extracts, phosphorylated mannanoligosaccharides, phosphites and acibenzolar-S-methyl, besides traditional fungicides, were used for the disease control. The intensity of downy mildew on leaves and bunches, productivity, total number of bunches per plot, average weight of bunch and berry and analytical characteristics of grapes were assessed during the 2007/2008 and 2008/2009 seasons. Phosphites provided protection against downy mildew, and the yield was similar that of to the treatment with traditional fungicides. Treatments based on phosphorylated mannanoligosaccharides, acibenzolar-S-methyl and plant extracts showed no effective control of downy mildew. The alternative products tested do not influence the analytical quality of the grapes, but generally provide lower average weight of bunches and berries than the treatment with fungicides.